Characterization of the Metabolic Fate of Datura metel Seed Extract and Its Main Constituents in Rats - Xia, Cong; Liu, Yan; Qi, Hai; Niu, Lulu; Zhu, Yuxuan; Lu, Wanying; Xu, Xinyi; Su, Yongjian; Yang, Bingyou; Wang, Qi (Frontiers in Pharmacology, 2019)
Datura metel L. has been frequently used in Chinese traditional medicine. However, little is known on the chemical composition and in vivo metabolism of its seeds. In the present study, using the strategy “chemical analysis, metabolism of single representative compounds, and metabolism of extract at clinical dosage” that we propose here, 42 constituents were characterized from D. metel seeds water extract. Furthermore, the metabolic pathways of 13 representative bioactive compounds of D. metel seeds were studied in rats after oral administration of D. metel seeds water extract at clinical dosage (0.15 g/kg). These included three withanolides, two withanolide glucosides, four amides, one indole, one triterpenoid, one steroid, and one sesquiterpenoid, and with regards to phase II metabolism, hydroxylation, (de)methylation, and dehydrogenation reactions were dominant. Furthermore, the metabolism of D. metel seeds water extract provided to rats at clinical dosage was investigated by liquid chromatography-tandem mass spectrometry based on the above metabolic pathways. Sixty-one compounds were detected in plasma, 83 in urine, and 76 in fecal samples. Among them, withanolides exhibited higher plasma exposure than the other types. To our knowledge, this is the first systematic study on the chemical profiling and metabolite identification of D. metel seeds, including all compounds instead of single constituents.